PENGARUH VARIETY SEEKING DAN E-WOM TERHADAP BRAND SWITCHING PADA PENGGUNA SAMSUNG KE IPHONE (Studi Pada Generasi Z di Kota Semarang) - Anisa Labiybah; Andi Wijayanto; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2025)
Smartphones are the result of technological developments that are progressing rapidly. The rapid progress of information technology encourages smartphone manufacturers to compete to create superior products. This makes consumers have many choices in choosing a smartphone. According to IDC data in the 3rd quarter of 2021/2022 and the Top Brand Award for Teens in 2022/2023, Samsung is in the top position. However, its YoY and index have decreased, which means that there is a decrease in shipments, market share, mind share, and commitment share. In contrast, the iPhone actually experienced a significant increase. The sample in this study amounted to 100 Generation Z respondents in Semarang City using Samsung smartphones who switched brands to iPhones. Data analysis in this study was processed using SPSS version 26. This study produces findings that show that variety seeking and e-wom partially and simultaneously have a positive and significant effect on brand switching from Samsung to iPhone. This study suggests that Samsung can increase product launches and innovative features to reduce the level of variety seeking and increase e-wom activities through providing product information and cooperation with users to share positive experiences in order to increase its competitiveness on social media.